Diversidad de razas de Colletotrichum lindemuthianum en Antioquia y evaluación de germoplasma de frijol crema-rojo por resistencia a antracnosis - Santana, GE; Mahuku, George S. (2002)
Diversity of Colletotrichum lindemuthianum races in Antioquia and evaluation of cream-red bean germplasm for anthracnose resistance. To verify the composition of Colletotrichum lindemuthianum races in east of Antioquia, 12 differential bean varieties were used to characterize 15 isolates collected from naturally infected bean varieties. Eleven races were identified among the 15 isolates characterized, six of which (races 9, 131, 135, 139, 643, y 645) were characterized for the first time. In addition, we evaluated 49 bean genotypes collected from the bean genebank of CIAT and CORPOICA, as well as landraces from farmers in producing. These genotypes were evaluated under natural field conditions as well as in the greenhouse, using races 651 and 653, previously identified as the most virulent races from Antioquia. Only four genotypes (AND1084, SUG130, LAS106 and Diacol Catio) were resistant under both field and greenhouse conditions. These genotypes can be used as parents in breeding programs to introduce anthracnose resistant genes to bean genotypes with commercial seed types.